Analysis of the Effect of Nano-SiO2 and Waterproofing Agent on the Water Transportation Process in Mortar Using NMR - Tao Meng; Huadong Wei; Kanjun Ying; Menghua Wang (Applied Sciences, 2020)
Moisture diffusion in cement-based materials significantly impacts its durability. In this study, we analyzed the effect of adding a waterproofing agent and nano-SiO2 (NS) on the water transportation process in mortar using capillary water absorption tests and nuclear magnetic resonance (NMR) technology. The results indicate that the combined action of the waterproofing agent and nano-SiO2 drastically reduce the capillary water absorption coefficient and have a more significant impact than only adding the waterproofing agent. The moisture diffusion in different sections of the mortar during the water absorption process is obtained from the NMR test results and two function models. Comparative studies indicate that the NMR test results have good correlation with the capillary water absorption test results and provide accurate process data. The NMR analysis results offer a new analytical method to characterize the porosity of cement-based materials by continuously monitoring small-pitch sections.